Prostate cancer in men under 50: the impact of race/ethnicity and family history - Lechuang Chen; Yu Zhang; Qing H. Meng (Annals of Medicine, 2025)
Background Prostate cancer remains a significant global public health concern. It is the most common cancer and the second leading cause of cancer death among men in the United States. Current guidelines offer varying recommendations on prostate cancer screening, and most are focused on men aged 50–69. In this study, we examined key risk factors for prostate cancer in men under 50, emphasizing race/ethnicity and family history to better understand the distribution of higher-grade disease in this younger population.Methods This retrospective analysis utilized data from our hospital’s prostate cancer screening program collected between 2014 and 2024. In our cohort, a total of 312 men under 50 years of age underwent prostate biopsy. We assessed the association of Gleason scores, race/ethnicity, family history, and PSA levels using descriptive statistics analyses.Results Among 312 participants, the largest subgroup was White or Caucasian (n = 202, 64.7%), followed by Black or African American (n = 47, 15.1%), Hispanic or Latino (n = 46, 14.7%), and Asian or Pacific Islander (n = 17, 5.5%). Black or African American men showed a higher proportion of Gleason 7 and above compared with other racial/ethnic groups. A positive first-degree family history was also more frequent among Black or African American men and was correlated with elevated Gleason scores and elevated PSA levels in multiple racial/ethnic categories.Conclusion In our cohort of men under 50, both race/ethnicity and a positive family history are closely associated with higher-grade prostate cancer. These findings suggest that younger men from high-risk backgrounds may benefit from early detection strategies.